2005
DOI: 10.3748/wjg.v11.i27.4148
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plasma ghrelin levels inHelicobacter pylori-colonized, interleukin-1-receptor type 1-homozygous knockout (IL-1R1-/-) mice

Abstract: Ghrelin secretion triggered by H pylori infection might be suppressed by IL-1beta, the release of which is also induced by the infection, resulting in the body weight loss of mice with H pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…It has been reported to have endocrine and nonendocrine actions [3][4][5][6][7] , although there have been some contrary results. Also, the regulation of ghrelin secretion and its exact role have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been reported to have endocrine and nonendocrine actions [3][4][5][6][7] , although there have been some contrary results. Also, the regulation of ghrelin secretion and its exact role have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have shown that ghrelin is secreted from hypothalamus, pituitary, endocrine pancreas islets, bowel, kidney, heart and testis [1,2] . Besides stimulating GH secretion, ghrelin has been reported to have other endocrine and nonendocrine actions, including stimulation of lactotroph and corticotroph secretion, effects on the gonadal axis, cardiovascular activity, influence on behavior and sleep, modulation of cell proliferation, repression of apoptosis, and orexigenic effects [3][4][5][6][7] . However, most of these studies used animal models and there were some discrepancies in the results.…”
Section: Introductionmentioning
confidence: 99%
“…The plate was incubated for a further 30 min at room temperature under shade conditions. After the reaction, a reagent was added to stop the reaction, and the absorbance of each well was measured at 450 nm [15].…”
Section: Measurement Of Plasma Ghrelin Levelsmentioning
confidence: 99%
“…A TaqMan ® quantitative real-time RT-PCR was performed to detect preproghrelin mRNA and GAPDH mRNA with the ABI PRISM 7700 Sequence Detection System (PE Applied Biosystems, Foster City, CA) [15,22]. The following primers were used to amplify the preproghrelin mRNA: ghrelin-F (5'-GGA ATC CAA GAA GCC ACC AGC-3'), ghrelin-R (5'-GCT CCT GAC AGC TTG ATG CCA-3') and ghrelin-Taq (5'-FAM-AAC TGC AGC CAC GAG CTC TGG AAG GC-TAMRA-3'); to amplify GAPDH mRNA as the internal control, the following primers were used: GAPDH-F (5'-TTC AAC GGC ACA GTC AAG GC-3'); GAPDH-R (5'-GCC TTC TCC ATG GTG GTG AAG-3') and GAPDH-Taq (5'-FAM-CCC ATC ACC ATC TTC CAG GAG CGA GA-TAMRA-3').…”
Section: Measurement Of Preproghrelin Mrna Expression In the Stomachmentioning
confidence: 99%
See 1 more Smart Citation